Frontispiece: π–π Stacking Interaction in an Oxidized CuII–Salen Complex with a Side‐Chain Indole Ring: An Approach to the Function of the Tryptophan in the Active Site of Galactose Oxidase. Issue 32 (7th June 2019) - Oshita, Hiromi; Suzuki, Takashi; Kawashima, Kyohei; Abe, Hitoshi; Tani, Fumito; Mori, Seiji; Yajima, Tatsuo; Shimazaki, Yuichi
Abstract : While the studies on the stacking interactions in proteins and metal complexes have been widely developed and have characterized mainly their static aspects, this article focuses on the electron transfer dependent on‐off switching of the stacking interaction between the indole and coordinated phenolate moieties, as seen in the function of the active site tryptophan of galactose oxidase. The present results should cast a new light on stacking interactions and grow up to a big chemistry, as if cherry blossoms come out at once. Spring has come in the chemistry of weak interactions. For more details, see the Full Paper by Y. Shimazaki et al. on page 7649 ff.